An Efficient Synthesis of Dichotomine A via Cyclization of L-Tryptophan Derivative - Xiao Shi, Xiu; He, Dian; Bai Li, Shao; Lei, Xin; Yang, Huan (Asian Journal of Chemistry, 2013)
A new synthetic method for dichotomine A is reported. The key step of the synthetic process is the efficient cyclization of L-tryptophan derivative via a modified Bischler-Napieralski reaction which aluminium chloride is used as a mild catalyst. Dichotomine A is obtained in 5 steps and 63.9 % yield.